Quando O SANTO chama: O terreiro de umbanda como contexto de aprendizagem na prática - Renata Silva Bergo (2010)
What a umbanda temple located in a borough in the outskirts of Belo Horizonte (MG) has to reveal to us about learning processes is the theme of this theses. Thought from an ethnographic incursion into the universe of daily practices of umbandists, the study tries to identify and describe a native model of making umbandists process to be comprehended through the theoric help of Lave e Wenger (1991) as a type of situated learning, and through Ingold (2000) as education of attention and process of habilitation. It is, therefore, a research about ways of thinking and acting of the members of a community of practice specific, keeping in its core the discussion regarding learning as part of the process of becoming, making an umbandist.